2020
DOI: 10.3847/1538-4357/ab9106
|View full text |Cite
|
Sign up to set email alerts
|

The Age Dependence of Mid-infrared Emission around Young Star Clusters

Abstract: Using the star cluster catalogs from the Hubble Space Telescope program Legacy Extragalactic UV survey (LEGUS) and 8 μm images from the IRAC camera on the Spitzer Space Telescope for five galaxies within 5 Mpc, we investigate how the 8 μm dust luminosity correlates with the stellar age on the 30-50 pc scale of star-forming regions. We construct a sample of 97 regions centered at local peaks of 8 μm emission, each containing one or more young star cluster candidates from the LEGUS catalogs. We find a tight anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(55 citation statements)
references
References 96 publications
11
44
0
Order By: Relevance
“…8 Myr and 80 Myr), a visual check of the 24µm emission at the location of the cluster is used as the deciding factor. The 24 µm dust emission has been shown to follow closely the 8 µm emission in HII regions (Relaño & Kennicutt 2009), and the latter has been shown to decrease dramatically with increasing age of the star cluster out to at least 300-400 Myr (Lin et al 2020). Sharma et al (2011) showed that most of the 24 µm bright sources in M33 are generally younger than 10 Myr.…”
Section: Mamentioning
confidence: 84%
“…8 Myr and 80 Myr), a visual check of the 24µm emission at the location of the cluster is used as the deciding factor. The 24 µm dust emission has been shown to follow closely the 8 µm emission in HII regions (Relaño & Kennicutt 2009), and the latter has been shown to decrease dramatically with increasing age of the star cluster out to at least 300-400 Myr (Lin et al 2020). Sharma et al (2011) showed that most of the 24 µm bright sources in M33 are generally younger than 10 Myr.…”
Section: Mamentioning
confidence: 84%
“…In the same Fig. 1, we compare the position of sources in our catalogs with the position of MIR compact regions, selected in Spitzer 8µm observations by Lin et al (2020). We remind that 8µm observations have a much lower resolution than the HST one, and that sources in the Lin et al (2020) catalog were selected to have some HST cluster counterpart.…”
Section: Sources With Compact Paschen-β Emissionmentioning
confidence: 99%
“…1, we compare the position of sources in our catalogs with the position of MIR compact regions, selected in Spitzer 8µm observations by Lin et al (2020). We remind that 8µm observations have a much lower resolution than the HST one, and that sources in the Lin et al (2020) catalog were selected to have some HST cluster counterpart. Overall, the different catalogs cover similar regions of the galaxy; however, some of the Lin et al (2020) sources are not present in our catalogs.…”
Section: Sources With Compact Paschen-β Emissionmentioning
confidence: 99%
See 2 more Smart Citations